Marine red algae of Pacific Mexico - Dawson, E.Y. (Los Angeles, California The University of Southern California Press, 1962)
contents: part 6. Rhodymeniales. Part 7. Ceramiales: Ceramiaceae, Delesseriaceaepart 8. Ceramiales: Dasyaceae, Rhodomelaceae
Keywords: Algae; Red algae